Penetration depth of sodium hypochlorite into dentinal tubules influenced by different agitation systems - Karad, Keyur; Kolhe, Swapnil; Gulve, Meenal; Aher, Gayatri; Kolhe, Priyanka (Endodontology : journal of Indian Endodontic Society, 2021)
Objectives: To compare the effect of different agitation systems on the penetration depth of sodium hypochlorite into dentinal tubules: An in vitro study. Background: Studies have found the presence of bacteria in dentinal tubule up to 200 μ. Passive irrigation using NaOCl may not adequately eliminate these bacteria. Hence, it is mandatory to use agitation systems during irrigation and disinfection of root canal. Materials and Method: Eighty extracted teeth with single canals were used. Standardized access cavity preparation and working length determination were done using visual method. All canals were instrumented till #30, 6%. All samples were immersed in crystal violet dye. The samples were randomly divided into four groups depending on the type of agitation system used (n = 20): Group A: manual dynamic agitation (MDA), Group B: EndoActivator (EA), Group C: EndoUltra (EU), and Group D: EndoVac (EV). Each agitation system was used with 5 ml of 5.25% NaOCl, and each tooth was sectioned into two halves. These sections were analyzed under a stereomicroscope, and NaOCl penetration depth was measured at coronal, middle, and apical third levels. Statistical Analysis Used: Statistical analysis was performed using one-way ANOVA and Tukey's post hoc test. Results: At all levels of examination, EU significantly showed a maximum penetration depth of NaOCl throughout the length of root canal, followed by EA, MDA, and EV. Conclusion: Ultrasonic agitation using EU is the most effective method to disinfect the dentinal tubules throughout the length of root canal than EA and MDA. EV showed the least penetration depth of sodium hypochlorite.